TEACHING AND LEARNING VOCABULARY FROM A SEMANTIC ASPECT - Nurmurodova, Madina (Журнал иностранных языков и лингвистики, 2023)
The article is devoted to the theory of the teaching and learning vocabulary from a semantic aspect. The field method finds effective application in the study of the language of literary works. The need to expand the vocabulary of students is determined by various reasons. The surrounding life, reading books, newspapers, magazines, listening to radio and television programs enrich the knowledge of students, along with which often come unfamiliar words. The assimilation of knowledge at the same time involves the memorization of new words.